EFFECT OF REPUTATION AND WEB QUALITY ON CUSTOMER TRUST - Muhammad Zaki Rahman; Rifki Abdul Malik (Asosiasi Dosen Muda Indonesia, 2022)
This research is focused on the influence of reputation and web quality on customer trust in Shopee Customers, Galuh Ciamis University students. The method used in this study is an explanatory survey method with a descriptive quantitative approach. Meanwhile, to analyze the data obtained, descriptive and verification analysis were used including simple correlation coefficient analysis, multiple correlation coefficient analysis, multiple regression analysis, determination coefficient analysis, and hypothesis testing using significance test t-test, and F test. The results of the study showed reputation and web quality. effect both partially and simultaneously on customer trust in Shopee customers, Universitas Galuh Ciamis students. Meanwhile, from the calculation of the simple correlation coefficient analysis, the relationship level is low.